Representações de autoridade no grupo tropicalista - Lustosa, Maridulce Ferreira (2009)
This study it treats on pertinent questions to the authority, with specific visibility for the musical artistic group known as tropicalista, its concept, images of negation and its interlacements, through a dialogue in Richard Sennett. The research investigated the representations of the authority for tropicalista group in the decade of 1960, with the secular clipping of 1967 the 1969, period this that marked the time of youth of the majority of thetropicalistas actors. The factors that give meant the relation of the group with the authority are weaveeed historically by the events that they had marked the then world and by the social conditions and cultural objective especially in the space axle of the cities of São Paulo and Rio de Janeiro. The work is structuralized in three chapters. The first one has as heading the TROPICALISTAS: IT IS FORBIDDEN TO FORBID points out the tropicalista movement in the panorama of the Brazilian culture, the concern that this youth had in the construction of a proper image and the importance of the antropofágico movement for the intellectual elaborations and artistic musical comedy of this group. As it has as heading PANIS ET CIRCENCES: IMAGE OF a NEW TIME and develops the description and the interpretation of the images that had collaborated with the analysis of the relation between the authority and the tropicalistas and the third chapter, STOPS BEYOND the FORMS: The TROPICALISMO AND ITS SPEECHES have the attention directed toward the analysis of the speeches, from its musical creations and depositions.